Investigating a Sparse Peripheral Display in a Head-Mounted Display for VR Locomotion - Hashemian, Abraham M.; Kitson, Alexandra; Nguyen-Vo, Thinh; Benko, Hrvoje; Stuerzlinger, Wolfgang; Riecke, Bernhard E. (2018 IEEE Conference on Virtual Reality and 3D User Interfaces (VR), 2018)
Head-Mounted Displays (HMDs) provide immersive experiences for virtual reality. However, their field of view (FOV) is still relatively small compared to the human eye, which adding sparse peripheral displays (SPDs) could address. We designed a new SPD, SparseLightVR2, which increases the HMD's FOV to 180° horizontally. We evaluated SparseLightVR2 with a study (N=29) by comparing three conditions: 1) no SPD, where the peripheral display (PD) was inactive; 2) extended SPD, where the PD provided visual cues consistent with and extending the HMD's main screen; and 3) counter-vection SPD, where the PD's visuals were flipped horizontally during VR travel to provide optic flow in the opposite direction of the travel. The participants experienced passive motion on a linear path and reported introspective measures such as sensation of self-motion. Results showed, compared to no SPD, both extended and counter-vection SPDs provided a more natural experience of motion, while extended SPD also enhanced vection intensity and believability of movement. Yet, visually induced motion sickness (VIMS) was not affected by display condition. To investigate the reason behind these non-significant results, we conducted a follow-up study and had users increase peripheral counter-vection visuals on the central HMD screen until they nulled out vection. Our results suggest extending HMDs through SPDs enhanced vection, naturalness, and believability of movement without enhancing VIMS, but reversed SPD motion cues might not be strong enough to reduce vection and VIMS.
Keywords: 2-page conference paper; Riecke; Riecke_2018; abraham-hashemian; bernhard-riecke; conferencePapers; iat802; iat802_fall2016; leaning-based interfaces; motion-cueing; navi-search-in-VR; naviChair; poster; proj--motionCueingInterfaces; proj--naviSearchInVR; short conference paper; thinh-nguyen-vo; wolfgang-stuerzlinger